Representasi sensualitas simbolis pada iklan alat kontrasepsi: (Analisis Semiotika Roland Barthes) - Afrisyah, Misbahul; Kurniawan, Bima (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This study aims to examine the symbolic representation of sensuality in contraceptive advertisements, specifically the "Sutra Gerigi Lebih Berasa #MantapMantapMakinMesra" version of Sutra Condom ads, through Roland Barthes' semiotic analysis. This method is chosen to reveal hidden meanings in the visual symbols and text of the advertisement using concepts such as denotation, connotation, and myth. The research findings indicate that the advertisement positions women as subordinate objects by highlighting sensitive body parts and employing sensual gestures to attract viewers' interest. The discussion reveals that this representation reinforces stereotypes that women merely serve to satisfy men's desires and exploits women's beauty and body shapes for commercial purposes. The conclusion of this study is that such contraceptive advertisements strengthen negative stigmas against women and demonstrate that their beauty and sexual appeal continue to be exploited in modern advertising.